3D Printing of Freestanding Overhanging Structures Utilizing an In Situ Light Guide. Issue 8 (29th April 2019) - Lim, Jongkyeong; Kim, Young Kwon; Won, Dong‐Joon; Choi, In Ho; Lee, Sangmin; Kim, Joonwon
Abstract: Conventional 3D printing methods require supporting material as a sacrificial layer to form a stable structure and to obtain the desired final product. The use of the supporting material causes several problems, such as damage to the surface of materials during the removal process. This results in considerable waste of materials, energy, and time. This paper proposes a new 3D printing method to create a freestanding overhanging structure that does not require supporting material. The printed hydrogel structure can guide and transmit light by utilizing an in situ light guide within the hydrogel, similar to an optical fiber. The results show that the curved angle at which the structure can grow at a constant rate can be controlled from 0° to ≈60°. In addition, hierarchical, branched, and helical structures can be easily created because the growth direction of the structure is freely adjustable. In future, by applying the proposed 3D printing method to a variety of functional material designs, the aim is to provide opportunities for various practical applications such as soft actuators, tissue engineering, and sensors. Abstract : A new 3D printing method to create a freestanding overhanging structure that does not require supporting material is proposed. The printed hydrogel structure can guide and transmit light by utilizing an in situ light guide within the hydrogel, similar to an optical fiber. This method can fabricate various 3D overhanging structures such as hierarchical, branched, and helical structures.